Utilização da flutamida em indicações não aprovadas pela ANVISA : aspectos referentes à segurança, efetividade, avaliação do risco e estratégias para contorná-lo - Figueiredo, Patrícia Mandali de (2004)
Flutamide is a non steroid anti-androgenic drug used to treat prostate cancer patients. When it became commercialized, more than 10 years ago, the hepatotoxic effect of flutamide was already recognized. In March and July 2002, the first cases of deaths in young females caused by fulminant hepatitis associated to off label use of this substance (magistral drug) was reported to the Pharmacovigilance Office/ANVISA. Up to now, similar cases were not described in the international literature. This work aimed to review and add information about the adequate use of flutamide by female patients to treat hirsutism, acne and androgenetic alopecia. To identify the standard prescriptions and the reported serious reactions in females worldwide, an extensive research through data provided by OMS was conducted. Moreover, using active search we looked for new local cases and review the information from package insert of all commercialized drugs in Brazil to analyze if the required and relevant information warning patients against the serious hepatic risks were provided. Finally, a survey with the prescribers was carried on through the web to identify the available information about the use of this drug in females and to make comparisons with data from the literature about the safety and efficacy of the use of this substance. The results showed that this substance is also used off label by women from other countries, who also presented serious adverse reactions. However, it was not reported any case of female death. Over the study, new cases of obituary occurred in Brazil, despite all analyzed package insert explain that this substance should not be used by females and mention serious hepatic reactions. The answers of the prescribers to the survey indicated that flutamide is an important therapeutic arsenal and that the risk of the use of this substance seem to have been underestimated. We concluded that flutamide is effective for the women treatment which it has been used. However, the threats of this drug point to the unacceptable use of this drug when applied for the esthetic finality.